2006
DOI: 10.1089/jmf.2006.9.196
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Oyster Mushroom Pleurotus ostreatus on Human Androgen-Independent Prostate Cancer PC-3 Cells

Abstract: Twenty species of edible mushrooms and three purified mushroom polysaccharides were screened for their antitumor potential on human androgen-independent cancer PC-3 cells. A water-soluble extract (POE) prepared from the fresh oyster mushroom Pleurotus ostreatus produced the most significant cytotoxicity on PC-3 cells among the mushroom species tested. At the same time, POE induced a rapid apoptosis on PC-3 cells detected with annexin V-fluorescein isothiocyanate flow cytometry when the cells were exposed to PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…Another study demonstrated that PO expresses marked antihepatoma and antisarcoma activities [21]. Treatment with the water extract of PO (150  μ g mL −1 ) induced phosphatidyl serine translocation from the inner membrane to the outer membrane after as little as 2 h and then induced apoptosis in human prostate cancer PC-3 cells [6]. Recently, the water-soluble polysaccharide extracted from the fruiting bodies of PO was shown to have obvious antitumor activity; they inhibited human HeLa cells in a concentration-dependent manner [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that PO expresses marked antihepatoma and antisarcoma activities [21]. Treatment with the water extract of PO (150  μ g mL −1 ) induced phosphatidyl serine translocation from the inner membrane to the outer membrane after as little as 2 h and then induced apoptosis in human prostate cancer PC-3 cells [6]. Recently, the water-soluble polysaccharide extracted from the fruiting bodies of PO was shown to have obvious antitumor activity; they inhibited human HeLa cells in a concentration-dependent manner [11].…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of PO suppresses the proliferation of breast and colon cancer cells via p53-dependent and p53-independent pathways [3]. The water-soluble polysaccharide of PO is capable of enhancing concanavalin A- or lipopolysaccharide-induced lymphocyte proliferation [4, 5] and induces apoptosis in human PC-3 androgen-independent cancer cells as well as human HT-29 colon cancer cells [6, 7]. DNA isolated from the fruit body of PO augmented NK cytotoxic activity in vitro and significantly increased the life span of mice with solid Ehrlich carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of Pleurotus species had higher antitumor activity toward lung cancer cells (A549). Recently, a potent antioxidant activity against both DPPH and ABTS radicals was detected in the ethanolic extracts of Pleurotus mushroom [73]. Many more reports are available indicating that oyster mushroom possesses antitumor activity of lectin isolated from P. citrinopileatus exerted potent antitumor activity in mice bearing sarcoma S-180.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Pleurotus sp. antitumor activity has been focused by several studies (Zhang et al , 2004; Gu and Sivam, 2006; Lavi et al , 2006; Sarangi et al , 2006; Jedinak and Sliva, 2008; Wolff et al , 2008; Dalonso et al , 2010). …”
Section: Introductionmentioning
confidence: 99%